Beyond the Canvas: An Exploration of Curriculum Design and Aesthetic Education in Fostering Aesthetic Development and Artistic Skills among Primary School Students - Malika AIT Nasser (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: This study aims to investigate the relationships between curriculum design, aesthetic education, student motivation, and students’ aesthetic development and artistic skills in Morocco’s primary schools. Specifically, it explores how curriculum design influences aesthetic development and artistic skills, examines the impact of aesthetic education on aesthetic development, and investigates the role of student motivation in mediating these relationships. Methodology: Using a qualitative approach, the study conducted semi-structured interviews with 25 primary school educators in Morroco to gather insights into their perspectives on curriculum design, aesthetic education, student motivation, and students’ aesthetic development and artistic skills. Thematic analysis was employed to analyze the interview data, identifying key themes and patterns related to the research questions. Findings: The findings reveal intricate connections between curriculum design, aesthetic education, student motivation, and students’ aesthetic development and artistic skills. Curriculum design plays a foundational role in shaping students’ aesthetic experiences, while aesthetic education and student motivation mediate the effectiveness of curriculum interventions in promoting aesthetic development and artistic skills. Implications/Novel Contribution: This research contributes to our understanding of the complex interplay between curriculum design, aesthetic education, student motivation, and students’ aesthetic development and artistic skills in primary schools. It underscores the importance of integrating aesthetic principles into curriculum design and fostering intrinsic motivation to optimize students’ aesthetic learning experiences. The findings have implications for educational practice, policy, and research, highlighting the need for holistic approaches to arts education that nurture students’ creativity, critical thinking, and aesthetic sensibilities.